MODAL SOSIAL MASYARAKAT DALAM PENGELOLAAN TEMBAWANG DI DESA PALOAN KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - anasia melia; emi roslinda; hari prayogo (Tengkawang : Jurnal Ilmu Kehutanan, 2022)
The management of tembawang by the community in Paloan Village has been carried out for generations. It is important to know social capital in the management of tembawang because tembawang is still maintained by the community even though commercially it does not provide anything significant to people's income. This study aims to examine and assess the characteristics of individuals in the community, examine the condition of social capital community in tembawang management, measure and analyze the relationship between individual characteristics and the elements of social capital, between social capital and its constituent elements and between social capital and tembawang management. in Paloan Village. This research was conducted by field observations, direct interviews with respondents and assisted by questionnaires that have been prepared as well as literature studies by collecting secondary data from various agencies and the results of previous studies related to the research. The level of social capital of the community was analyzed using the value interval equation. While the relationship of social capital was analyzed using the Sperman Rank coefficient test. The results showed that the level of social capital of the Paloan Village community was in the "medium" category. The relationship of community social capital in the management of tembawang has a "weak direction" relationship. This shows that the relationship of social capital is significantly related to the management of tembawang.  Keywords: Community, Management of tembawang, Social capital.AbstrakPengelolaan tembawang oleh masyarakat di Desa Paloan telah dilakukan secara turun temurun. Pentingnya untuk mengetahui modal sosial dalam pengelolaan tembawang karena tembawang masih tetap dipertahankan keberadaannya oleh masyarakat walaupun secara komersial tidak memberikan sesuatu yang signifikan terhadap pendapatan masyarakat. Penelitian ini bertujuan untuk mengkaji dan menilai karakteristik individu pada masyarakat, mengkaji kondisi modal sosial masyarakat dalam pengelolaan tembawang, mengukur dan menganalisis hubungan antara karakteristik individu dengan unsur-unsur modal sosial, antara modal sosial dengan unsur-unsur pembentuknya dan antara modal sosial dengan pengelolaan tembawang di Desa Paloan. Penelitian ini dilakukan dengan observasi lapangan, wawancara langsung dengan responden dan dibantu dengan kuesioner yang telah disusun serta studi pustaka dengan mengumpulkan data sekunder dari berbagai instansi dan hasil penelitian terdahulu yang berkaitan dengan penelitian. Tingkat modal sosial masyarakat dianalisis menggunakan persamaan selang nilai. Sedangkan hubungan modal sosial dianalisis menggunakan uji koefisien Peringkat Sperman. Hasil penelitian menunjukkan bahwa tingkat modal sosial masyarakat Desa Paloan dalam kategori “sedang”. Hubungan modal sosial masyarakat dalam pengelolaan tembawang memiliki hubungan yang “searah lemah”. Hal ini menunjukkan bahwa hubungan modal sosial berhubungan nyata dalam pengelolaan tembawang. Kata Kunci: Masyarakat, Modal sosial, Pengelolaan Tembawang